2010
DOI: 10.1097/fbp.0b013e32833b110b
|View full text |Cite
|
Sign up to set email alerts
|

Reference place conditioning procedure with cocaine: increased sensitivity for measuring associatively motivated choice behavior in rats

Abstract: Place conditioning is widely used to study the conditioned rewarding effects of drugs. In the standard version, one reward (cocaine) is compared to no reward (saline). A modified variant of this task, "reference-conditioning" procedure, compares two potentially rewarding stimuli (high versus low cocaine dose). There has been little research on the utility of this procedure. Experiment 1 used the standard protocol with saline administered before confinement to the reference compartment of a place-conditioning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Mice lacking the delta opioid receptors can therefore use various morphine-predicting stimuli, either internal or discrete but not spatial, to retrieve a CPP to morphine. Such ability is in line with the view that conditioned associations in place conditioning not only encode the affective properties of the unconditioned stimulus (US) but also include information regarding the feature of the US (Bevins and Murray 2011; Corbit and Balleine 2005; Delamater and Holland 2008; Reichel et al 2010). …”
Section: Discussionsupporting
confidence: 72%
“…Mice lacking the delta opioid receptors can therefore use various morphine-predicting stimuli, either internal or discrete but not spatial, to retrieve a CPP to morphine. Such ability is in line with the view that conditioned associations in place conditioning not only encode the affective properties of the unconditioned stimulus (US) but also include information regarding the feature of the US (Bevins and Murray 2011; Corbit and Balleine 2005; Delamater and Holland 2008; Reichel et al 2010). …”
Section: Discussionsupporting
confidence: 72%
“…This habituation day was used as a preconditioning (PC) test to verify the unbiased construction of the apparatus. Conditioning compartments were assigned in an unbiased manner such that each rat had equal opportunity to receive cocaine in their naturally least or most preferred side ( Mueller and Stewart, 2000 ; Tzschentke, 2007 ; Reichel et al, 2010 ). Placements were counterbalanced according to chamber color (black/white) and whether the rats received cocaine or saline injections on the first or second day of conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio was calculated with the following formula: [(time in CS+/(time in CS- + CS+)) × 100] ( Reichel and Bevins, 2008 ). Saline control rats values were randomly assigned a CS+ and CS- compartment for comparison purposes ( Reichel et al, 2010 ). Preference ratios were then compared against a hypothetical mean of 50%.…”
Section: Methodsmentioning
confidence: 99%
“…To further assess dose dependency in CPP studies, besides measuring time to extinction, future studies should address the question whether, in animals conditioned with a higher dose of the conditioning drug, lower challenge doses can reinstate extinguished CPP. Related to this, a recent study demonstrated that rats conditioned with sub-threshold doses of cocaine were able to discriminate between these sub-threshold doses using a procedure of reference place conditioning [32] . The latter procedure therefore provided an alternative method of demonstrating dose dependency between different doses of drugs in CPP, and of comparing rewarding effects of different doses or different drugs.…”
Section: Discussionmentioning
confidence: 99%